1997
DOI: 10.1523/jneurosci.17-15-05820.1997
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor and Fibroblast Growth Factor-2 Have Different Effects on Neural Progenitors in the Adult Rat Brain

Abstract: Neurons and glia are generated throughout adulthood from proliferating cells in two regions of the rat brain, the subventricular zone (SVZ) and the hippocampus. This study shows that exogenous basic fibroblast growth factor (FGF-2) and epidermal growth factor (EGF) have differential and site-specific effects on progenitor cells in vivo. Both growth factors expanded the SVZ progenitor population after 2 weeks of intracerebroventricular administration, but only FGF-2 induced an increase in the number of newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
761
2
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,118 publications
(827 citation statements)
references
References 65 publications
53
761
2
9
Order By: Relevance
“…Infusion of FGF2 into the lateral ventricle resulted in enhanced neurogenesis within the SVZ and a subsequent increase in the number of new neurons in the olfactory bulb, whereas similar infusion of EGF resulted in a decrease of new neurons in the olfactory bulb. The latter was associated with a significant increase of astrocytes in the neighboring striatum [84,92]. These observations are in contrast with a previous report demonstrating an increase in neural recruitment to the olfactory bulb and a recruitment of new neurons to the striata following intraventricular infusion of EGF [93].…”
Section: Mitogens Can Trigger Adult Neurogenesis In Vivocontrasting
confidence: 98%
See 1 more Smart Citation
“…Infusion of FGF2 into the lateral ventricle resulted in enhanced neurogenesis within the SVZ and a subsequent increase in the number of new neurons in the olfactory bulb, whereas similar infusion of EGF resulted in a decrease of new neurons in the olfactory bulb. The latter was associated with a significant increase of astrocytes in the neighboring striatum [84,92]. These observations are in contrast with a previous report demonstrating an increase in neural recruitment to the olfactory bulb and a recruitment of new neurons to the striata following intraventricular infusion of EGF [93].…”
Section: Mitogens Can Trigger Adult Neurogenesis In Vivocontrasting
confidence: 98%
“…Neural stem cells from the adult subventricular zone can be expanded and maintained in vitro under the influence of fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF); these observations suggested that FGF2 and EGF might also act in vivo [84][85][86][87][88]. Indeed, knockout mice for FGF2 or transforming growth factor-α, a ligand for EGF receptor, exhibit decreased neurogenesis in the SVZ, and fewer neurons recruited to the olfactory bulb [89,90].…”
Section: Mitogens Can Trigger Adult Neurogenesis In Vivomentioning
confidence: 99%
“…Other astroglial-inducing factors, such as leukemia inhibitory factor (LIF), Notch-Delta, and basic fibroblast growth factor (bFGF) can initiate the astrocyte differentiation program only in E15 or older cortical progenitors, not in early (for example, E11), neurogenic progenitors 8,[13][14][15][16][17][18][19] . In E11 CNS neural progenitors, both Notch-Delta and bFGF function instead as pro-proliferation and anti-differentiation factors 15,18,[20][21][22] .LIF-induced Jak-STAT signaling is a critical part of the astrogliogenic machinery 23,24 . Mouse knockout studies have demonstrated that genetic deficiency in major components of this pathway, including LIF, its receptors LIFRÎČ and gp130, or the signaling molecules STAT1/3, leads to impaired astroglial differentiation [25][26][27] (Supplementary Fig.…”
mentioning
confidence: 99%
“…Moreover, infusion of FGF-2 into the lateral ventricle of adult rats stimulates neurogenesis in the SVZ and increases the number of neurons migrating from SVZ to the olfactory bulb (Kuhn et al, 1997). Although basal and stroke-induced (Jin et al, 2004) neurogenesis decline with age, neuronal precursors in the SVZ retain the ability to respond to FGF-2 with an increase in neuronal proliferation (Jin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%